KLITIK –NYA DALAM BAHASA INDONESIA - I Wayan Pastika (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
The –nya clitic is discussable in terms of not only microlinguisctic domains (phonology, morphology and syntax) but also macrolinguistic perspectives like pragmatics and sociolinguistics. In terms of microlinguistics, there are three important findings of the –nya clitic structure : it can appear (a) as a genitive form, (b) as a definite marker, and (c) as a third person pronoun attached to different word categories (verbs, adjectives, and adverbs). Pragmatically speaking, the –nya clitic can distinguish ‘the old information’ from ‘the new one’ overtly and covertly. From the sociolinguistic point of view the –nya clitic is functioned to avoid the use of the second person that directly threatens the interlocutor’s face. The –nya clitic is also used to measure the degree of closeness between the addresser and the addressee (speech participants): the use of -nya indicates closer relationship (as in bukunya mana?), whereas the use of second person forms indicates formality (as in Dimana Buku Anda?). In informal situations, the speaker tends to choose the third person–nya as a marked form instead of the second person forms such as Anda, kamu, Saudara,  Bapak, Ibu, and Dik, which are unmarked. Therefore,  the –nya clitic is grammatically, pragmatically, and sociolinguistically very dynamic in different speech registers.